Entrepreneurs, IPros and the Talent Eco-System - Syrett, Michel (Senate Hall, 2015)
With independent professionals and budding entrepreneurs now forming the fastest growing proportion of the workforce, large corporations are losing out on the best talent. This article, based on research conducted for The Economist book Managing Talent, highlights the efforts talent managers are making to access and retain the skills of professionals workers who are no longer motivated by the idea of life-long corporate careers. Two approaches are highlighted in depth. The first is business incubation schemes, where corporates buy stakes in business start-ups founded by young entrepreneurs, using selection methods that are far removed from the assessment centres and graduate induction campaigns of old. The second is 'alumni' schemes operated by large management consultancies, where staff wishing to pursue independent careers are encouraged to draw on the resources of the parent company and share their expertise in collaborative ventures. In the process, corporations are extending the boundaries of who is, or is not, a part of the organisation, turning on its head outdated notions of 'core-periphery' manpower planning. Indeed, in the case of 'freelance entrepreneurs', there are early indications that forward-looking employers are choosing them in favour of 'insular' internal high fliers. "If you join McKinsey, you join for life even though you are not necessarily still employed here" - Emily Lawson, Head of Global Human Capital Practice, McKinsey & Company Keywords: IPros, freelance entrepreneurs, intrapreneurs, talent management, business incubation schemes, business alumni schemes
Keywords: Ipros|freelance entrepreneurs|intrapreneurs|talent management|business incubation schemes|business alumni schemes